2004
DOI: 10.4315/0362-028x-67.8.1806
|View full text |Cite
|
Sign up to set email alerts
|

Sulfites—A Food and Drug Administration Review of Recalls and Reported Adverse Events

Abstract: Sulfite-sensitive individuals can experience adverse reactions after consuming foods containing sulfiting agents (sulfites), and some of these reactions may be severe. In the 1980s and 1990s, the U.S. Food and Drug Administration (FDA) acted to reduce the likelihood that sulfite-sensitive individuals would unknowingly consume foods containing sulfites. The FDA prohibited the use of sulfites on fruits and vegetables (except potatoes) to be served or presented fresh to the public and required that the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 5 publications
0
37
0
3
Order By: Relevance
“…It has long been known that sulfites are a potent enzymatic browning inhibitor that change PPO structure and therefore irreversibly inhibit PPO activity (Sayavedrasoto & Montgomery, 1986). However, the FDA prohibited the use of sulfites on fruits because of their toxicity so they are not an option to inhibit enzymatic browning in pawpaw pulp (Timbo, Koehler, Wolyniak, & Klontz, 2004), which led to alternatives such as ascorbic acid or thiol-containing compounds (Pilizota & Subaric, 1998).…”
Section: Correlations Between Ppo Phenolics Flavonoids and Color Omentioning
confidence: 99%
“…It has long been known that sulfites are a potent enzymatic browning inhibitor that change PPO structure and therefore irreversibly inhibit PPO activity (Sayavedrasoto & Montgomery, 1986). However, the FDA prohibited the use of sulfites on fruits because of their toxicity so they are not an option to inhibit enzymatic browning in pawpaw pulp (Timbo, Koehler, Wolyniak, & Klontz, 2004), which led to alternatives such as ascorbic acid or thiol-containing compounds (Pilizota & Subaric, 1998).…”
Section: Correlations Between Ppo Phenolics Flavonoids and Color Omentioning
confidence: 99%
“…Sulfites, benzoates, propionates, nitrites and nitrates are the commonly used preservatives for food products [5][6][7]. It has been reported that these chemicals induce adverse effects in human such as stomach cancer and acidity [4][5][6][7]. Due to these adverse effects, lactate is used as a preservative for food products related to meat, poultry and fish [1][2][3][4].…”
Section: Introductionmentioning
confidence: 97%
“…Sulfites, benzoates, propionates, nitrites and nitrates are the commonly used preservatives for food products [5][6][7]. It has been reported that these chemicals induce adverse effects in human such as stomach cancer and acidity [4][5][6][7].…”
Section: Introductionmentioning
confidence: 98%
“…Sulfites are one of the most effective chemical preservatives to inhibit browning; however, the FDA has prohibited the use of sulfites in fruits and vegetables labeled as “fresh” or intended to be served in the raw form (FDA 2011) due to the risk of severe allergic reactions in individuals highly sensitive to sulfites (Timbo and others 2004). …”
Section: Introductionmentioning
confidence: 99%